2001
DOI: 10.1051/0004-6361:20010514
|View full text |Cite
|
Sign up to set email alerts
|

Closed loop performance of a layer-oriented multi-conjugate adaptive optics system

Abstract: Abstract. The dynamic properties of a layer-oriented multi-conjugate adaptive optics system are examined. It is shown that such a system is stable and closes the loop. A simplified analysis of the achievable correction is presented, in order to define the conditions in which the layer-oriented approach is equivalent to other linear reconstruction schemes. It is found that this approach is equivalent to an optimum one, under certain assumptions, but still retaining the potential advantages of such a novel schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…New techniques could be proposed in the future by passing the limitation imposed by the number of DMs. For example, alternative solutions such as the layer oriented MCAO (Ragazzoni et al 2000b; (Diolaiti et al 2001) and hopeful but the sky coverage obtained with only NGSs has not yet been calculated in this case. Unfortunately, it seems that the problem of the large number of DMs necessary to correct a large FOV has still to be solved.…”
Section: Cmentioning
confidence: 99%
“…New techniques could be proposed in the future by passing the limitation imposed by the number of DMs. For example, alternative solutions such as the layer oriented MCAO (Ragazzoni et al 2000b; (Diolaiti et al 2001) and hopeful but the sky coverage obtained with only NGSs has not yet been calculated in this case. Unfortunately, it seems that the problem of the large number of DMs necessary to correct a large FOV has still to be solved.…”
Section: Cmentioning
confidence: 99%
“…It is highly estimated that a better performance should be achievable with an additional DM used to correct the high-altitude turbulence, which can be immediately realized by the proposed PT-MCAO. As discussed by Diolaiti et al, 3 this layer-oriented GLAO system is a linear reconstruction and its achieved correction is optimal according to the same criterion with that of the star-oriented approach. In fact, in a converging closed loop system with a sufficiently high correction bandwidth, good correction can be achieved within a few iterations.…”
Section: Discussionmentioning
confidence: 99%
“…Two different MCAO systems were proposed until now: star-oriented 1 and layer-oriented 2 approaches. Diolaiti et al 3 showed that when the FOV is discretized according to the directions of guide stars (GSs), the layeroriented and the star-oriented correction have equivalent performances.…”
Section: Introductionmentioning
confidence: 99%
“…This is true for both the layer oriented and star oriented approaches. Any mis-placement in altitude of the DM, and in the layer oriented case, also of the sensors, smoothes out the spatial frequencies of the higher orders as shown by [13] or [14]. We are conducting SCIDAR measurements at Mt.…”
Section: Altitude Conjugationmentioning
confidence: 99%